Promising benefits of six-month Phaeodactylum tricornutum microalgae supplementation on cognitive function and inflammation in healthy older adults with age-associated memory impairment - Goodbody, Emily; Maury, Jonathan; Doolan, Andrea; DunnGalvin, Gillian; Kakilla, Charles; Pradelles, Rémi; Dinan, Timothy G. (Frontiers in Aging, 2025)
IntroductionAging is often associated with cognitive decline and memory impairment, with several factors including inflammatory cytokines and oxidative stress markers implicated in this natural process. Microalgae extracts are a natural source of many bioactive compounds that reduce inflammation and oxidative stress, and represent an innovative dietary approach to ameliorate age-related cognitive decline and memory impairment. This proof-of-concept CONSORT-compliant, double-blind, randomized controlled study was conducted to evaluate the effect of daily supplementation of microalgae extract on cognitive function, mood, stress and inflammation of healthy older adults with mild cognitive impairment over a 24-week period.MethodsSixty-six volunteers with age-associated memory impairment (AAMI; age 55–75 years) were randomly assigned to ingest a placebo (PL, maltodextrin) or 550 mg of Phaeodactylum tricornutum (Pt) extract (4.4 mg of fucoxanthin, PUFAs and saturated fatty acids). Participants performed the COMPASS cognitive test battery to measure spatial, working, and episodic memory, attention, vigilance, and executive function. Sleep quality, mood, stress states and inflammation markers were also evaluated. All endpoints were collected at baseline, weeks 12 and 24.ResultsThere were no between-group differences for the primary outcome (Corsi Block Span Score) or other cognitive function parameters, at either 12 week or 24 weeks. However, within groups, 24 weeks of daily intake of microalgae extract derived from Phaeodactylum tricornutum attenuated age-induced readouts in Stroop task overall reaction time (p = 0.005; Cohen’s d = 0.8) and Word recall delayed score (p = 0.010; Cohen’s d = 0.5) as compared to baseline week 0, while no significance was reported for these readouts in the placebo group. Similar findings were reported for participants’ perceived stress (p = -0.04; Cohen’s d = 0.4). There was a significant decrease in blood hs-CRP from 3.9mg/L to 2.1mg/L following 24-weeks of Pt extract supplementation as compared to placebo (p = 0.002; Cohen’s d = 0.8), while there was no adverse impact on safety clinical blood tests or reported side effects, with the product deemed safe and tolerable.DiscussionThe findings suggest promising benefits of daily intake of microalgae extract on cognitive function and immune markers in older subjects with AAMI. Future research into the preventive role of Pt extract in age-assocaited cognitive decline is warranted.Clinical Trial RegistrationIdentifier #NCT04832412.